Meningkatkan Laba Bagi Pengusaha Sembako di Desa Kudaile Slawi dengan Menerapankan Etika Bisnis Islam - Sarja, Sarja (Madaniyah, 2023)
An entrepreneur or businessman must have Islamic business ethics, this is an important element in every business activity. have Islamic business ethics a demand in making decisions or solving problems in terms of the staple food business in kudaile village because it has a positive influence in advancing and facing business competition. The application of Islamic business ethics really needs to be emphasized to the owners of staple food stores. This research method is field research with a descriptive qualitative approach. Data obtained from interviews with grocery store owners in kudaile slawi village. The results showed that the profits of staple food owners increased when applying Islamic business ethics well, this was proven by data testing Through the application of business ethics that are in accordance with Islam proven to be able to increase profits. An entrepreneur or businessman needs principles that must be applied in business ethics, namely tawhid, balance or alignment, and responsibility The most important thing for a staple food entrepreneur in kudaile slawi is ethics, ethics is an important part that an entrepreneur or businessman must have, because ethics is seen as a demand in making decisions or solving problems in terms of business.